Randomised prostate cancer screening trial: 20 year follow-up. (31st March 2011) - Sandblom, Gabriel; Varenhorst, Eberhard; Rosell, Johan; Löfman, Owe; Carlsson, Per
Abstract : Objective To assess whether screening for prostate cancer reduces prostate cancer specific mortality. Design Population based randomised controlled trial. Setting Department of Urology, Norrköping, and the South-East Region Prostate Cancer Register. Participants All men aged 50-69 in the city of Norrköping, Sweden, identified in 1987 in the National Population Register (n=9026). Intervention From the study population, 1494 men were randomly allocated to be screened by including every sixth man from a list of dates of birth. These men were invited to be screened every third year from 1987 to 1996. On the first two occasions screening was done by digital rectal examination only. From 1993, this was combined with prostate specific antigen testing, with 4 µg/L as cut off. On the fourth occasion (1996), only men aged 69 or under at the time of the investigation were invited. Main outcome measures Data on tumour stage, grade, and treatment from the South East Region Prostate Cancer Register. Prostate cancer specific mortality up to 31 December 2008. Results In the four screenings from 1987 to 1996 attendance was 1161/1492 (78%), 957/1363 (70%), 895/1210 (74%), and 446/606 (74%), respectively. There were 85 cases (5.7%) of prostate cancer diagnosed in the screened group and 292 (3.9%) in the control group. The risk ratio for death from prostate cancer in the screening group was 1.16 (95% confidence interval 0.78 to 1.73). In a Cox proportional hazard analysis comparing prostate cancer specific survival in the control group with that in the screened group, the hazard ratio for death from prostate cancer was 1.23 (0.94 to 1.62; P=0.13). After adjustment for age at start of the study, the hazard ratio was 1.58 (1.06 to 2.36; P=0.024). Conclusions After 20 years of follow-up the rate of death from prostate cancer did not differ significantly between men in the screening group and those in the control group. Trial registration Current Controlled Trials, ISRCTN06342431 .